Spontaneously Occurring micronuclei in infiltrating ductal carcinoma of breast: A potential biomarker for aggressive phenotype detection?1. Issue 4 (11th October 2011) - Goel, Shubham; Bhatia, Alka; Dey, Pranab
Abstract Chromosomal instabilities (CIN) manifesting as structural or numerical alterations in the chromosomes are common in malignancies like breast cancer. Assessment of CIN in breast cancer may help to understand its etiopathogenesis. Micronucleus (MN) scoring and aneuploidy have been used to assess the presence of CIN in lymphocytes of various malignancies in the past. In this study, spontaneously occurring MN were counted in epithelial cells on fine needle aspiration cytology (FNAC) smears from 50 patients with benign and malignant breast lesions. Further, the ploidy status and S‐phase fraction (SPF) of the samples was determined by flow cytometry. All these were then correlated with grades of breast cancer at cytology. Most IDC cases showed variable number of MN (n = 16, MN mean = 9.3), in contrast to the benign lesions (n = 26) where they were consistently absent. Aneuploidy and SPF analysis also showed a significant difference between benign (n = 10, mean DNA index [DI] = 0.96 ± 0.04, mean SPF= 8.07% ± 2.93) and malignant (n = 10, mean DI = 1.5 ± 0.41, mean SPF = 25.05% ± 10.35) lesions. On statistical analysis, a positive correlation was observed between the grades of IDC and presence of aneuploidy and high SPF (P‐values < 0.05); however, the difference between the MN scores of grade 2 and 3 cancers was not significant. The study suggests that MN scoring and aneuploidy may be used to assess the presence of underlying CIN in IDC on FNAC smears. Further, collectively they may be explored for their role as biomarkers for predicting the tumor behavior in the breast cancer patients. Diagn. Cytopathol. 2013;41:296–302. © 2011 Wiley Periodicals, Inc.